Profile Of Combinatorial Reasoning Ability Using Description Tests In Physics Learning Of High School Students - Feby Dwi Cahyanti; Yetti Supriyati; Anggara Budi Susila (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2020)
Abstract. The purpose of this study is to describe the combinatorial reasoning ability of high school students in physics learning and to determine the characteristics and the instrument quality of combinatorial reasoning using written test. The research method used is Analyze Design Development Implementation and Evaluation (ADDIE). The written test has the characteristics to measure the ability of deductive hypothesis between variables, to determine the process of combining student reasoning in solving the sequence and series problems and use all possible alternative answers in solving problem systematically based on the stage of combinatorial reasoning. The combinatorial reasoning test was validated by expert and physics teachers. The research participants are student in six of high school grade eleven who had learn all of the concept in one terms. The results of the research show combinatorial reasoning ability of high school students that 24% of students had a high level of combinatorial reasoning, in this case the students are able to fulfill the combinatorial stages. 64% of students were in the medium category and 10.83% of students were in the low category